#DRCL midnight children. 01, Envoy from the East - Sakamoto, Shin'ichi, 1971- (VIZ Media, LLC, 2023)
"In this beautiful, evocative, and often surreal retelling of Bran Stoker's Dracula, a fearsome enemy arrives from the east, bringing with it horrors the likes of which have never been seen in the British Empire. Standing opposed are Wilhelmina "Mina" Murray and her stalwart companions, united in a cabal that eclipses gender, nationality, and station until the day that they can achieve victory. As Mina struggles to find her place as Whitby School's first and only student, a devilish horror is unleashed upon the academy and its unsuspecting students: Count Dracula. However, when this unspeakable evil lays claim to her beloved Lucy Westenra, Mina stands ready to join forces with her fellow students and fight against it with everything she has."--Back cover.